High speed data acquisition system using raspberry pi and ADC unit - Nazrul Azli, Razali (2021)
A data acquisition system (DAQ) is a system that takes real-world measurements such as temperature, pressure, distance, and more in a function of time. The processes involved are reading the analog value from a sensor, signal conditioning if necessary, converting the analog signal into a digital signal, and analyzing the digitized signal for further processing. A value that is registered by the DAQ system is considered a sample, and the speed at which the DAQ system executes the entire operation for one sample can be defined by the sampling rate, and this sampling rate can influence the smoothness of the waveform created. Sometimes, these data are too difficult to be processed using traditional methods which are due to the data is too big, too fast, or too complex. The applications that highlight the speed of the DAQ system are critical are quality control, audio system applications involving noise cancellation, radar, navigation applications, and more. Lately, the usage of Raspberry Pi products for electronic projects is increasing. This is because Raspberry Pi itself is a computer or accurately an ARM computer that can be connected to the internet network. However Raspberry Pi cannot receive an analog signal as a data signal, that is why it needs an ADC unit for the conversion. In this project, we will be developing a Raspberry Pi-based oscilloscope using Arduino Nano as an ADC unit and the result of the analysis will be determined by how far the frequency which it can measure.